Socio-ecological resilience in peasant agro-ecosystems in Sumapaz Province (Cundinamarca) - Fonseca Carreño, Nelson Enrique; Fonseca Carreño, Jorge Armando (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This article evaluates the socio-ecological resilience in agro-ecosystems in the Province of Sumapaz, through the typification of indicators of threat, vulnerability and response capacity, according to the agro-ecological-based practices implemented there. The concept of the Holistic Risk Index was used to evaluate the level of socio-ecological resilience in 20 farmers under biophysical and socioeconomic criteria and the Wilcoxon Test contrasted differences between agroecological and conventional systems where p < 0.05 values show the difference. Therefore, the degree of resilience was estimated through 21 indicators, 8 are presented with values > 1 that do not favor resilience conditions and 13= < 1 that are favorable. The risk index presents agro-ecological systems with values of 3.1 ±5.0 and conventional values of 0.7 ±1.9; which demonstrates high vulnerability. It is concluded that there is a transition towards agroecological systems that reduce energy and resources and resist to perturbations and alterations of the anthropic type.